Metabolic responses to glucoprivation induced by 2-deoxy-D-glucose in Brycon cephalus (Teleostei, Characidae) - Figueiredo-Garutti, M. L.; Capilla, E.; Vicentini-Paulino, MLM; Gutierrez, J.; Souza, RHS; Moraes, G.; Navarro, I (Springer, 2004)
The effects of functional cytoglucopenia provoked by 2-deoxy-D-glucose (2-DG) were studied in adult Brycon cephalus, an omnivorous fish from the Amazon Basin in Brazil. Glycogen content in liver and muscle as well as plasmatic glucose, free fatty acids (FFA), insulin, and glucagon were measured. After 48 h fasting, an intraperitoneal saline injection (NaCl 0.6 g/100 ml) was administered to control fish, whereas the experimental group received 2-DG, dissolved in saline, in the dosage of 80 mg/kg (0.487 mmol/kg) or 150 mg/kg (0.914 mmol/kg) body weight; injection volume was 5 ml in all treatments. Blood and tissue samples were taken immediately before, and 2, 8, 10, and 24 h after administration of the drug or saline. Fish injected with both doses of 2-DG showed a marked increase in glycemia levels. Liver and muscle glycogen decreased after 2-DG administration and reached their lowest values 10-24 h after injection, while in control animals no significant changes were observed. Elevation in plasma glucagon was observed only in response to the maximum dosage of 2-DG administered, especially 10 h and 24 h post-injection. Plasma insulin levels were lower in animals treated with the glucose analogue but only statistically significant 24 h after drug administration. In conclusion, the administration of the non-metabolizable glucose analogue 2-DG in B. cephalus is a stimulus to generate responses towards an increase in the glucose available to tissues, which is a characteristic of a fasting situation. All the above data support the interest of 2-DG administration as a model to study carbohydrate metabolism adjustment mechanisms in fish.
Keywords: 2-deoxy-D-glucose; glycemia; free fatty acids; insulin; glucagon